2018
DOI: 10.1038/s41598-018-36127-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Model for Ion Transport and Cytoplasm Conductivity of Chinese Hamster Ovary Cells

Abstract: In mammalian cells cytoplasm ion concentrations and hence cytoplasm conductivity is an important indicator of their physiological state. Changes in the cytoplasm conductivity has been associated with physiological changes such as progression of cancer and apoptosis. In this work, a model that predicts the effects of physiological changes in ion transport on the cytoplasm conductivity of Chinese hamster ovary (CHO) cells is demonstrated. We determined CHO-specific model parameters, Na+/K+ ATPase pumps and ion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 54 publications
(74 reference statements)
1
29
0
Order By: Relevance
“…(a) Mean force indices for different medium conductivities (0.17–0.45 S/m). Stars and circles indicate the obtained results in our previous work (Fazelkhah et al, , circles; Saboktakin Rizi et al, , stars). (b) Re { K CM } calculated using a double shell model as a function of medium conductivity (Salimi et al, ).…”
Section: Methodsmentioning
confidence: 66%
See 4 more Smart Citations
“…(a) Mean force indices for different medium conductivities (0.17–0.45 S/m). Stars and circles indicate the obtained results in our previous work (Fazelkhah et al, , circles; Saboktakin Rizi et al, , stars). (b) Re { K CM } calculated using a double shell model as a function of medium conductivity (Salimi et al, ).…”
Section: Methodsmentioning
confidence: 66%
“…Previous experimental and numerical analysis of CHO cells has shown that DEP measurement at 6 MHz is primarily sensitive to the cell's cytoplasm conductivity. In a medium with conductivity 0.42 S/m, other parameters such as cell size have a much less significant influence (Fazelkhah et al, ; Saboktakin Rizi et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations